Waging Insurgent Warfare : Lessons from the Vietcong to the Islamic State - Jones, Seth G (New York Oxford University Press, 2017)
There are over three dozen violent insurgencies around the globe today, including in such high-profile countries as Iraq, Syria, Afghanistan, and Ukraine. If we are to understand modern warfare, we need to understand insurgencies. Waging Insurgent Warfare weaves together an impressive analysis of how groups start, wage, and end insurgencies.
Include Index and Acknowledgment
Keywords: Insurgency -- Counterinsurgency -- Guerrilla warfare